2018
DOI: 10.12890/2018_000986
|View full text |Cite
|
Sign up to set email alerts
|

Non-Uremic Calciphylaxis: A Rare Diagnosis with Limited Therapeutic Strategies

Abstract: Calciphylaxis is a rare condition characterized by the emergence of non-healing skin ulcers secondary to arterial calcification and thrombosis, typically diagnosed in patients with end-stage kidney disease (ESKD). When it develops in patients without ESKD, it is called non-uremic calciphylaxis (NUC). The latter is an even rarer diagnosis with an uncertain pathophysiology and a high mortality rate (52%), mainly due to sepsis (50%). Cutaneous biopsy is diagnostic. Therapeutic measures recommended for NUC are lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 14 publications
0
29
0
4
Order By: Relevance
“…We identified 53 cases of NUC [5]- [6][7]which included 46 (86.79 %) individual case reports and 7 (13.20 %) case series Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 53 cases of NUC [5]- [6][7]which included 46 (86.79 %) individual case reports and 7 (13.20 %) case series Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies reported multiple conditions 18 (33.96 %) [8,5,9,10,11,[12][13][14]6,15,16,17,1819,20,21,22], [7]; define herein as patients suffering from more than two morbidities were assembled in multiple conditions. Other morbidities among the included studies were warfarin induced (7.54 %) [23,24,25 1).…”
Section: Fig 1 An Overview Of the Approach For Doing A Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient therapeutic procedures and evidence-based recommendations are needed especially for non-uremic CP, since therapeutic strategies can so far only be transferred from CUA treatment without a pathophysiological correlation. 27 Concepts of a modern wound management should be followed with special emphasis on debridement and prevention or early treatment of wound infections which are involved in the high mortality of CP patients due to sepsis. Non-adhesive modern wound dressings or products with silicone layer can be applied to the wound to enable an atraumatic dressing change and reduce pain.…”
Section: Treatmentmentioning
confidence: 99%
“…As the presented therapeutic strategies mainly derive from those for uremic CP, more efficient therapeutic measures and evidence-based recommendations are needed for non-uremic cases. 27 A clear diagnostic classification as CP is mandatory.…”
Section: Systemic Treatmentmentioning
confidence: 99%